Interplay of Endosomal pH and Ligand Occupancy in Integrin α5β1 Ubiquitination, Endocytic Sorting, and Cell Migration - Dmitri Kharitidi; Pirjo M. Apaja; Sanaz Manteghi; Kei Suzuki; Elena Malitskaya; Ariel Roldan; Marie-Claude Gingras; Junichi Takagi; Gergely L. Lukacs; Arnim Pause (Cell Reports, 2015)
Membrane trafficking of integrins plays a pivotal role in cell proliferation and migration. How endocytosed integrins are targeted either for recycling or lysosomal delivery is not fully understood. Here, we show that fibronectin (FN) binding to α5β1 integrin triggers ubiquitination and internalization of the receptor complex. Acidification facilitates FN dissociation from integrin α5β1 in vitro and in early endosomes, promoting receptor complex deubiquitination by the USP9x and recycling to the cell surface. Depending on residual ligand occupancy of receptors, some α5β1 integrins remain ubiquitinated and are captured by ESCRT-0/I, containing histidine domain-containing protein tyrosine phosphatase (HD-PTP) and ubiquitin-associated protein 1 (UBAP1), and are directed for lysosomal proteolysis, limiting receptor downstream signaling and cell migration. Thus, HD-PTP or UBAP1 depletion confers a pro-invasive phenotype. Thus, pH-dependent FN-integrin dissociation and deubiquitination of the activated integrin α5β1 are required for receptor resensitization and cell migration, representing potential targets to modulate tumor invasiveness.